Analisis Produksi Tanda (Semiotik) Pada Siswa Dibedakan dari Kemampuan Bahasa - Suci Yongki Setyowati; A Saepul Hamdani; Lisanul Uswah Sadieda (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Semiotics has an important role in supporting the success of mathematics problems solving. In mathematics everything that related to the signs, symbols and relations between symbols is called semiotics. In this study, semiotics means the ability producing signs including the symbolization process, the coding process and the meaning process as a part of a code system for communicating the information. The purpose of this study is to find out the detailed description of students' semiotic ability in solving the linear program problems which is distinguished from the language skill. Researchers tested the credibility and validity of the data using the triangulation source. The results of the study shows that students who have high language skills are able to do these three processes. So that the information conveyed from the results of the problem solving becomes a meaningful information. Students who have medium language skills have difficulty in the process of symbolization and meaning. Consequentlly, the information conveyed is incomplete. Meanwhile students who have low language skills have difficulty in these three processes. So that students have not been able to convey information from the results of their work.